2015
DOI: 10.1534/genetics.114.169680
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Cervical Vertebrae Blueprint Depends on theT(brachyury) Gene

Abstract: A key common feature of all but three known mammalian genera is the strict seven cervical vertebrae blueprint, suggesting the involvement of strong conserving selection forces during mammalian radiation. This is further supported by reports indicating that children with cervical ribs die before they reach reproductive age. Hypotheses were put up, associating cervical ribs (homeotic transformations) to embryonal cancer (e.g., neuroblastoma) or ascribing the constraint in cervical vertebral count to the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
2
12
0
2
Order By: Relevance
“…43 A study in Bos taurus (cattle) also confirmed that a heterozygous mutation in Tbxt is causative for vertebral and spinal dysplasia phenotype, which is associated with a reduced number of cervical vertebrae. 44 These observations are consistent with the cervical vertebral fusion phenotype of our CS028 patient with p.R16L mutation. In humans, a homozygous missense TBXT mutation, p.H171R, has been previously identified in three families with a syndrome consisting of sacral agenesis, a persistent notochordal canal and abnormal ossification of the vertebral bodies.…”
Section: Discussionsupporting
confidence: 90%
“…43 A study in Bos taurus (cattle) also confirmed that a heterozygous mutation in Tbxt is causative for vertebral and spinal dysplasia phenotype, which is associated with a reduced number of cervical vertebrae. 44 These observations are consistent with the cervical vertebral fusion phenotype of our CS028 patient with p.R16L mutation. In humans, a homozygous missense TBXT mutation, p.H171R, has been previously identified in three families with a syndrome consisting of sacral agenesis, a persistent notochordal canal and abnormal ossification of the vertebral bodies.…”
Section: Discussionsupporting
confidence: 90%
“…However, Postma and colleagues have recently reported on the involvement of T (brachyury) gene in the pathogenesis of an apparently monogenic form of NTD in humans encompassing sacral agenesis, abnormal ossification of the vertebral bodies and a persistent notochordal canal (Postma et al 2013). This is consistent with available data on the role of T in vertebral development (Ghebranious et al 2008;Kromik et al 2015). On the other hand, Kelley and colleagues reported in this journal an association between a common variant in T (rs2305089) and sporadic chordoma (Kelley et al 2014).…”
supporting
confidence: 71%
“…In spite of the physical and functional dysfunctions associated with VSD in the hind limbs and in the vertebral column, there was no concomitant observation of urogenital or skull defects. Lack of urogenital or skull defects was confirmed in a further study focussing on detailed post-mortem analysis of VSD-affected calves (Kromik et al, 2015). This is a unique feature of VSD, because tail defects in other breeds or species are frequently associated with particular malformations as can be seen, for example, in CTS in Belgian Blue cattle (Fasquelle et al, 2009) and the well-known Manx syndrome in cats (Deforest and Basrur, 1979).…”
Section: Discussionmentioning
confidence: 80%